ANALYSIS AND EVALUATION OF THE EFFICIENCY OF GEOLOGICAL AND TECHNOLOGICAL MEASURES IN THE FIELD OF EXPLORATION AND DEVELOPMENT OF GAS CONDENSATE FIELDS IN THE EAST USTYURT REGION - Hayitov , Odiljon Gafurovich; Orynbaev , Bakhtzhon Ametovich (Digital technologies in industry, 2025)
The article considers information on discoveries and fields under development in the Eastern Ustyurt region, where valuable geological, geophysical and field materials have been accumulated in the period 1960-2025. The article is also devoted to improving the efficiency of exploration and development of complex fields based on geological, geophysical and geological-field data , clarifying the structure of deposits taking into account the drilling of new appraisal and production wells , and carrying out geological and technological measures. When implementing geological and technical measures (GTM), modern advanced technologies have been introduced aimed at increasing the production of residual gas reserves from complex fields. In order to assess the effectiveness, the use of geotechnologies of the control method in the implementation of GTM is scientifically substantiated.